The influence of lactose and povidon on the formulation of tablet containing Kaempferia galanga L . extract by a wet granulation method - Kuswahyuning, Rina; Soebagyo, Sri Sulihtyowati (Indonesian Journal of Pharmacy, 2005)
Increasing use of Kaempferia galanga L. (Kencur) as a traditional medicine needs the development of more practical dosage form e.g. tablets. This study was conducted to observe the infuence of lactose as a filler and Povidon as a binding agent to the physical properties of the granules and to determine the optimum tablet formula for Kaempferia galanga L. extract by a wet granulation method. The use of factorial design with 2 factors (lactose and Povidon) and 2 levels (lactose : low level = 300% and high level = 450% of the extract weight, respectively; Povidon : low level = 0.3% and high level = 3% of the extract weight, respectively), it needed four formulas to produce granules of the Kaempferia galanga L. extract. Each of the granules of Kaempferia galanga L. extract was produced by a wet granulation method and was dried at 40-60°C for 24 hours. Dry granules were tested on their properties of flowability, compactibillity and water uptake.  Lactose significantly influenced the compactibillity and the water uptake, whereas Povidon significantly influenced the compactibillity, flowability and water uptake. Based on the contour plots of the physical properties of the granules and total responses, formula using 315% lactose and 2.98% Povidon of the extract weight, respectively, was chosen as the optimum tablet formula. Produced tablets had dark brown colour and weight uniformity with average weight of 373.60 ± 0.63 mg, hardness of 2.18 ± 0.192 kg, friability of 0.10 ± 0.011%, and disintegration time of 4.43 ± 0.147 minutes.Key words : Kaempferia galanga L. extract, tablet formula, lactose, Povidon